Trendy or Timeless? The Effect of Need for Uniqueness and Pressure on the Choice of Unique Products - Gonçalves, Dilney; Stamatogiannakis, Antonios; Calderón, Susan (UIB, 2017)
Consumers trying to satisfy their need for uniqueness (NFU) frequently choose between products with similar degrees but different durations of uniqueness: timeless versus trendy products. These choices are often made under pressure generated by time or product availability constrains, usually controlled by companies. Although NFU and pressure frequently co-exist in choices of unique products, their joint effect is unknown. Our research covers this gap and examines how NFU and pressure interact to affect choices between timeless and trendy products. Three studies show that high-NFU individuals under higher (vs. lower) pressure tend to choose timeless (vs. trendy) products. Pressure does not affect choices of low-NFU individuals. This interaction is mediated by the extent to which individuals focus on duration of uniqueness when making choices. A pilot field-study highlights the managerial relevance and novelty of our investigation. We discuss how managers can shape their marketing appeals to better manage their product portfolio.
Keywords: Need for uniqueness; Unique product choices; Uniqueness duration; Pressure; 53 Ciencias Económicas::5311 Organización y dirección de empresas ::5311.05 Marketing (comercialización); ODS 12 - Producción y consumo responsables